Effect of Thyme Essential Oil Components on the Structure Properties of Chitosan Films and Its Migration Mechanism - Bingxin ZHANG; Jing SUI; Lingdong PEI; Lingqi SU; Yong PENG (Shipin gongye ke-ji, 2023)
In order to investigate the migration mechanism of thyme essential oil components thymol, linalool and caryophyllene from chitosan films, the physical, antimicrobial, migration characteristics and chemical structure of chitosan composite films were evaluated. The results showed that thyme essential oil, thymol and caryophyllene improved the water resistance ability of chitosan film, among which the water vapor permeability of caryophyllene decreased by 15.04% compared with the control. Moreover, thymol and caryophyllene also decreased the swelling degree (decreased by 24.31% and 11.64%) and elongation at break (decreased by 13.46% and 27.88%) of composite films. However, the antibacterial properties of chitosan films were significantly (P<0.05) improved with the addition of active components, particularly with thyme essential oil. All essential oil components increased the endothermic peak temperature and improved the thermal stability of chitosan films. In comparison, the migration rate of essential oil components from composite film was faster in distilled water than that in 95% ethanol. The migration rate of thymol was the fastest, followed by essential oil and caryophyllene, and linalool had the least migration. FTIR showed strong hydrogen bond interaction between chitosan and thyme essential oil, thymol and caryophyllene. The study could provide a reference for further exploring the performance and structural differences of chitosan essential oil composite film.